Investigation on the Present Situation of Music Intangible Cultural Heritage in Bayannur City, Inner Mongolia - Zhang, Jing (International Journal of Social Sciences and Public Administration, 2024)
The protection of intangible cultural heritage (referred to as "intangible heritage") is an idea put forward by UNESCO to protect human cultural diversity in order to safeguard the overall value and long-term interests of mankind. Chinese excellent traditional culture is profound and varied, among which music is an important part of Chinese excellent traditional culture. There are four intangible music projects in Bayannur City, Inner Mongolia, but the overall level of inheritance and development is not high. The main problems are: the inheritors are seriously aging; The innovation level of "works" is low; Insufficient publicity and promotion, not closely integrated with the development of the times and the economy and society. Based on this, this paper puts forward several specific paths to promote the inheritance and development of music Intangible Cultural Heritage projects in this area: vigorously cultivate inheritors and support performance groups; Create new tracks that adapt to the development of the times; Use the modern Internet to publicize from the media platform and gradually realize digital preservation; Local colleges and universities should undertake the responsibility of "intangible heritage" protection and inheritance.